2020
DOI: 10.1093/nutrit/nuaa022
|View full text |Cite|
|
Sign up to set email alerts
|

Carnosine and histidine-containing dipeptides improve dyslipidemia: a systematic review and meta-analysis of randomized controlled trials

Abstract: Context Cardiovascular disease is a major public health problem and represents a significant burden of disease globally. Lifestyle interventions have their limitations and an intervention that will effectively address cardiovascular risk factors to help reduce this growing burden of disease is required. Objective Carnosine and other histidine-containing dipeptides (HCDs) have exerted positive effects on cardiovascular risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…[1][2][3] Carnosine (𝛽-alanyl-L-histidine), a naturally occurring dipeptide and over-thecounter food supplement, has recently emerged as a potential strategy for reducing DM2 and CVD risk factors. [4,5] Carnosine is mainly found in human skeletal muscle and carnosine supplementation is shown to improve muscle performance and exercise endurance. [6] Lower concentrations of carnosine are also found in other tissues and cells such as the brain, stomach, and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] Carnosine (𝛽-alanyl-L-histidine), a naturally occurring dipeptide and over-thecounter food supplement, has recently emerged as a potential strategy for reducing DM2 and CVD risk factors. [4,5] Carnosine is mainly found in human skeletal muscle and carnosine supplementation is shown to improve muscle performance and exercise endurance. [6] Lower concentrations of carnosine are also found in other tissues and cells such as the brain, stomach, and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In addition to previously known benefits of carnosine for muscle function, more recent animal studies have shown that carnosine reduces obesity and improves glucose metabolism, chronic lowgrade inflammation, lipid levels and peroxidation, atherosclerotic plaque instability, blood pressure, insulin resistance, and insulin secretion, along with increasing 𝛽-cell mass. [4,[9][10][11][12][13][14][15] We and others have also shown beneficial effects of carnosine supplementation on glucose and lipid metabolism in humans. [5,16,17] Molecular and animal research suggests that the beneficial effects of carnosine on these risk factors occur, at least in part, through its anti-inflammatory, anti-oxidative, and anti-glycating properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 23 Our two recent meta-analysis showed improvements in fasting glucose, haemoglobin A1c (HbA1c) and triglyceride levels in studies using carnosine as a part of the intervention. 24 25 Moreover, other human studies using carnosine reported improved quality of life, physical performance and cognitive function. 20 26 27 Despite several studies showing the beneficial effects of carnosine on cardiometabolic risk factors, several limitations exist in the current literature.…”
Section: Introductionmentioning
confidence: 98%